The diversity, composition and potential function of bacterial size fractions from maize and soybean farmland soils - Xuemei Hu; Chang Wang; Siyuan Wang; Yinghui Cao; Haofei Zhang; Chang Liu; He Sun; Yajun Gao; Shanshan Yang; Sanfeng Chen; Sen Du; Gehong Wei; et al. (Geoderma)
Agricultural soil microbiomes, with their varied cell sizes and metabolic capabilities, contribute significantly to differences in soil ecosystem functions and services. However, the relationships among bacterial cell size, community structure and nutrient turnover in agricultural soils remain unclear. This study categorized bacterial cells from maize and soybean fields into five distinct size fractions—F1 (>10 μm), F2 (3–10 μm), F3 (1–3 μm), F4 (0.4–1 μm) and F5 (0.2–0.4 μm)—using polycarbonate membrane filtration. High-throughput sequencing of the 16S rRNA gene and soil incubation subsequently revealed the taxonomic composition and potential functions of each size fraction. The results indicated that the bacterial diversity in maize field soil was greater than that in soybean field soil, with the F4 size fraction exhibiting the highest diversity and abundance in both soils, whereas the F1 size fraction showed the lowest. Proteobacteria dominated across all size fractions, and size-specific taxonomic distributions were observed: Myxococcota, Entotheonellaeota and Cyanobacteria were enriched in F1 and F2; Planctomycetota and Chloroflexi were enriched in F3; Bacteroidota, Verrucomicrobiota, Actinobacteriota and Firmicutes were enriched in F4 and F5. Before incubation, the qPCR of functional genes showed that the F1–F3 fractions exhibited highly active ammonia oxidation (F1, F2) and ammonification (F3), while the F4 fraction presented highly efficient organic P mineralization, when compared to other fractions. After incubation, qPCR and soil property analyses revealed that the F4 fraction exhibited highest increase in cell numbers and regulated C and P turnover through the secretion of BG and AKP, whereas the F1 fraction consistently maintained high ammonia oxidation capacity. These findings illustrate that bacterial taxa vary in cell size and nutrient turnover processes under different land-uses, thereby deepening our understanding of the bacterial ecology in farmlands.